2023
DOI: 10.3390/polym15143041
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Modulation of Cell Morphology and Phenotype of Diseased Human Cells towards a Healthier Cell State Using Lignin

Abstract: Despite lignin’s global abundance and its use in biomedical studies, our understanding of how lignin regulates disease through modulation of cell morphology and associated phenotype of human cells is unknown. We combined an automated high-throughput image cell segmentation technique for quantitatively measuring a panel of cell shape descriptors, droplet digital Polymerase Chain Reaction for absolute quantification of gene expression and multivariate data analyses to determine whether lignin could therapeutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To determine if there were quantitative significant differences in shape descriptors (area, length, width, circularity, aspect ratio, roundness, and solidity), single-cell macrophage analysis was performed using a Fiji-based analysis algorithm ( 13 , 29 ). When comparing different groups of macrophages, the violin box plots ( Figure 5 ) revealed that the GM-CSF/TNFα/IFNγ-M1 (largest) and GM-CSF-M1 macrophages were larger in cell area than the other groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To determine if there were quantitative significant differences in shape descriptors (area, length, width, circularity, aspect ratio, roundness, and solidity), single-cell macrophage analysis was performed using a Fiji-based analysis algorithm ( 13 , 29 ). When comparing different groups of macrophages, the violin box plots ( Figure 5 ) revealed that the GM-CSF/TNFα/IFNγ-M1 (largest) and GM-CSF-M1 macrophages were larger in cell area than the other groups.…”
Section: Resultsmentioning
confidence: 99%
“…those inflamed and degenerated diseased human cells could be reverted to a healthier cell shape via therapeutic modulation and their healthier cell shape correlated with positive changes in major fibrosisand inflammatory-regulating genes (29). Thus, our method provides a simple and cost-effective means of capturing cellular responses by quantitating cell morphology.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations